(untitled) (Research, Society and Development, 2022)
In recent years, digital technologies have been gaining ground in various sectors of society. Ease of access and greater interaction with digital media have provided important advances in routine and interaction between people. In this sense, digital technologies present themselves as tools capable of contributing significantly to the process of training and human development. Although most schools recognize the contributions that digital tools provide in society, they sin when they resist implementing them in their pedagogical practices. To carry out this work, scientific articles, laws and decrees related to the theme were analyzed. This article alerts and explains the importance of using digital media, including the production of videos by the students themselves, as a teaching methodology. Thus, this article aims to explain the importance of video production in the school environment and explain how these videos can be used as a learning assessment tool by teachers.